Not a stranger to the dark: discrimination against autistic students and employees. Issue 1 (7th April 2021) - Lorenz, Timo; Brüning, Chelsea Rebecca; Waltz, Mitzi; Fabri, Marc
Abstract : Purpose: The purpose of this paper is to reveal barriers and their coherences between discrimination and self-perceived employability which students and employees on the autism spectrum often face and need to overcome. These include discrimination based on disability, when applying for a job or retaining employment. This research located barriers in three different categories: formality – problems that focus on organizational structures in the application process; social – communication and interaction problems; and job demand barriers – obstacles that epitomize work-related strains. Design/methodology/approach: Barriers and discrimination can prevent individuals from accessing the labor market which can lead to severe consequences for an individual on the autism spectrum, such as poverty, social deprivation or lack of health promotion and equal treatment. Self-perceived employability can be regarded as an additional strength, as it describes the perception of an individual's own skills and versatility to acquire and keep a job. In total, 53 German-speaking individuals on the autism spectrum participated in an online survey. Findings: Results showed statistically significant coherences between both, formality and social barriers with discrimination. Formality barriers also indicated statistically significant coherences with self-perceived employability. A mediation model with discrimination as mediator between each category of barriers and self-perceived employability was examined. The non-significant results suggest that discrimination does not work as a superior construct but as a sole influence next to barriers and self-perceived employability. Originality/value: Individuals on the autism spectrum epitomize a less common research approach. Moreover, diversity policies and practices in the workplace often do not focus on including individuals on the autism spectrum even though the employment rates for this specific group of potential highly qualified employees were reported to be consistently lower when compared to any other group of disabled people. Findings suggest possible starting points for future research, which are discussed alongside practical strategies to overcome barriers and change discriminatory attitudes toward skilled individuals on the autism spectrum.